HUBUNGAN PERILAKU WIRAUSAHA DENGAN KUALITAS PRODUK INDUSTRI KECIL MENENGAH (IKM) KERAJINAN TANGAN KOTA PONTIANAK - Irfani Az-Zahra; Warneri Warneri; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the relationship between entrepreneurial behavior and the quality of the Small and Medium Industries of Pontianak City Handicrafts. The method used in this research was descriptive method with a form of quantitative study of relationship studies (interrelationship studies). The population in this study is Pontianak Small and Medium Industries consumers. The sampling technique uses incidental sampling. Which respondents are sampled for research are; (a) consumers who are at least 17 years old, (b) consumers who have made a repeat purchase of the product at least 2 times. The data collection tool used uses direct and indirect communication techniques, namely observation of owners of Small and Medium Industries. Pontianak City Hand, questionnaire to Pontianak Kota Small and Medium Industries  consumers and documentation. While data processing techniques use Pearson correlation. The results of the research in the field can be concluded that that there was a positive relationship between entrepreneurial behavior and product quality. The significance of the calculation was 0.001 <0.05, the alternative hypothesis was accepted and the correlation relationship in the table was known to be 0.520 which means that the variables of entrepreneurial behavior with the quality of the products of the Small and Medium Industries Pontianak City have a moderate relationship.Keywords: Entrepreneurial Behavior, Product Quality